Analisis Faktor-Faktor Penyebab Siswa Melakukan Pelanggaran dan Penanggulangannya di Sekolah SMP TMI Roudlotul Qur’an 3 Sekampung - Yuli Habibatul Imamah (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
This research aims to find out several forms of violations of school rules and how to deal with students who violate rules at TMI Roudlotul Qur'an 3 Sekampung Middle School. The method used in this research is qualitative field research. Data collection uses triangulation (interviews, observation and documentation). The data taken was based on interviews with teachers and students at TMI Roudlotul Qur'an 3 Sekampung Middle School which were used as research objects. Then it is supported by observation data and strengthened by documentary evidence. Based on the research results, it can be concluded that first, the forms of violation of school rules at TMI Roudlotul Qur'an 3 Sekampung Middle School are often arriving late to school, still using inappropriate school attributes, skipping class during school hours, and there are still many alpha students. Second, the students' own internal factors still prioritize laziness and a lack of awareness that studying is very important. Third, environmental factors, this also influences the good and bad character of the student. The way to deal with students who violate school rules is that the teacher gives a direct warning by providing direction and motivation so that students change for the better. Providing special warnings in the form of letters or agreements given to students and parents by the school principal or guidance counselor so that students are reluctant to repeat the violations that have been made.